Preparation of hydrogel from the hydroalcoholic root extract of Premna integrifolia L. and its mediated green synthesis of silver nanoparticles for wound healing efficacy - Verma P.; Dixit J.; Singh C.; Singh A.N.; Singh A.; Tiwari K.N.; Muthu M.S.; Nath G.; Mishra S.K. (My University, 2025)
The current investigation concentrated on the fabrication of silver nanoparticles through the root of Premna integrifolia L. The antibacterial and wound healing effects of their silver nanoparticles-hydrogel and root extract-hydrogel were evaluated. The hydroalcoholic root extract of P. integrifolia was enriched with crocetin, ferulic acid, oleanolic acid, oleic acid, syringic acid, and vanillin. The silver nanoparticles were biosynthesized through secondary metabolite-enriched hydroalcoholic root extract (5 %) when mixed with 1 mM AgNO3 and kept under sunlight for 10 minutes. They showed an optimum surface plasmon resonance (SPR) at 447 nm. The aldehyde, phenol, and primary amine groups of the extract reduce silver cations into nanoparticles. The nanoparticles band gap of 2.06 eV showed their semi-conductance behavior. The nanoparticles were spherical, uniformly distributed, and stable. The nanoparticles had a good roughness profile and 57.55 % elemental silver. The silver nanoparticles-hydrogel (10 %) showed an efficient 11±0.11 nm zone of inhibition of S. aureus in comparison to the root extract-hydrogel (10 %), i.e., 9±0.15 nm. The nanoparticles-hydrogel and the root extract-hydrogel did not show noticeable symptoms of acute dermal toxicity. The nanoparticles-hydrogel (10 %) and the root extract-hydrogel (10 %) healed 99.9 % and 97.3 % of the S. aureus- infected wound, respectively. The nanoparticle-hydrogel efficiently induced re-epithelialization in the dermis of S. aureus-infected wound compared to the extract-hydrogel. The nanoparticle-hydrogel enhanced the rate of wound closure. © 2024 Elsevier Ltd